Cepacia Syndrome in a Non-Cystic Fibrosis Patient - Naomi Hauser; Jose Orsini (Case Reports in Infectious Diseases)
Burkholderia (formerly Pseudomonas) cepacia complex is a known serious threat to patients with cystic fibrosis, in whom it has the potential to cause the fatal combination of necrotizing pneumonia, worsening respiratory failure, and bacteremia, known as Cepacia syndrome. The potential for this pathogen to infect non-cystic fibrosis patients is limited and its epidemiology is poorly understood. Previously reported cases of severe Burkholderia cepacia complex lung infection in immunocompetent hosts include pneumonia, bronchiectasis, pyopneumothorax, and cavitary lesions. We present a case of a 64-year-old man with Streptococcus pneumoniae community-acquired pneumonia whose hospital course was complicated by developing cavitary lung lesions, bacteremia, and acute respiratory distress syndrome. Repeated tracheal aspirate and blood cultures grew Burkholderia cepacia. Our case appears to be the first report of Cepacia syndrome in a patient without cystic fibrosis. This report raises concern regarding the potential severity of pulmonary Burkholderia cepacia complex infection and the need to broaden clinicians’ suspicion for Cepacia syndrome. A framework to help diagnose and treat infected non-cystic fibrosis individuals may be useful.